PENGGUNAAN MEDIA KUARTET CERDAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV - Syaripudin, Asep; Gusrayani, Diah; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2017)
The result of study at fourth grade in SDN 2 Sadapaingan, Ciamis to the matter of distribution natural resources at region is still low. It was because of learning process did not use media. One of solution to solve problem is used media as â€œKuartet Cerdasâ€ for improve of students school grades. The research uses the methodology of action grade folks by Kemmis and MC. Taggart. From preliminary data study result of students from 19 people just seven people (37%) completed in archived a score of above 70 as KKM, the standard proportion for completing the material. On the cycle I students who completed about 11 people (58%), cycles II students who completed 14 people (74%), and the cycle III students who completed 16 people (84%). The act of buttoning that â€œKuartet Cerdasâ€ media can improve outcomes in the subject matter distribution IPS natural resources at the region nation.